2017
DOI: 10.21470/1678-9741-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Spinal Artery Syndrome Following Coronary Artery Bypass Grafting: a Case Report

Abstract: We present a patient with unstable angina candidate for coronary artery bypass grafting. Saphenous vein graft was used in obtuse marginal and left internal mammary artery to left anterior descending artery properly. After surgery, the patient experienced flaccid paralysis of lower limb and impaired sensation of touch and warmth of knee and below. A computed tomography angiogram of lower limbs and thoracolumbar magnetic resonance imaging showed no abnormality. Based on the symptom, clinical diagnosis of anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Bilateral paresis and loss of pain and temperature sensation with preservation of proprioception and vibratory sensation below the lesion are the typical characteristics [Müller 2012]. Mirhosseini et al [Mirhosseini 2017] reported a 61-year-old patient, who underwent hemiplegia in both lower extremities (muscle strength grade was zero) on the first day after surgery. Computer tomography angiography (CTA) showed multiple atherosclerotic plaques in the aortic artery, but no embolism; this patient had a long history of diabetes mellitus (DM) and hypertension and peripheral arterial diseases (PAD).…”
Section: Resultsmentioning
confidence: 99%
“…Bilateral paresis and loss of pain and temperature sensation with preservation of proprioception and vibratory sensation below the lesion are the typical characteristics [Müller 2012]. Mirhosseini et al [Mirhosseini 2017] reported a 61-year-old patient, who underwent hemiplegia in both lower extremities (muscle strength grade was zero) on the first day after surgery. Computer tomography angiography (CTA) showed multiple atherosclerotic plaques in the aortic artery, but no embolism; this patient had a long history of diabetes mellitus (DM) and hypertension and peripheral arterial diseases (PAD).…”
Section: Resultsmentioning
confidence: 99%
“…However, our patient exhibited diffuse arteriosclerosis of the thoracic and abdominal arteries, known as "shaggy aorta." Some reports have shown paraplegia due to spinal cord ischemia in patients with shaggy aorta and/or abdominal aorta and peripheral artery disease who undergo aortic non-touch surgeries such as coronary artery bypass grafting [3][4][5][6]. Regardless of the type of operation, the rate of aortarelated complications, including spinal cord ischemia, is increased in patients with a shaggy aorta [7].…”
Section: Discussionmentioning
confidence: 99%